1976
DOI: 10.1139/v76-033
|View full text |Cite
|
Sign up to set email alerts
|

Stereomutation of a 1,2,3-triketone: an example of an asymmetric reaction

Abstract: The 1,2,3-triketone PhC(Me)2COCOCOPh has been synthesized from mandelic acid in seven steps. Its proton magnetic resonance spectrum features a sharp six-proton methyl singlet at room temperature which broadens considerably at low temperatures but is not resolved into two peaks at 173 K. Similar dynamic behaviour is observed for the monoketone PhC(Me)2COPh. It is concluded that the barrier to interconversion of enantiomeric tricarbonyl helical conformations is significantly less than 7 kcal/mol. The rotation–ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1976
1976
2001
2001

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…Conversion of β-dicarbonyl compounds to monobromo derivatives followed by replacement of bromine has received a new lease on life with the introduction of dimethyl sulfoxide as a mild reagent for replacing such activated bromine atoms by a carbonyl oxygen. These include 1,1-dimethyl-1,4-diphenylbutanetrione (15), used by Wolfe et al 25 in their investigation of possible helical conformations of the trione chain (see section VII.B), and a variety of simple triones (R 1 ) alkyl, aryl; R 2 ) alkyl, aryl, ester), prepared by Dahn and co-workers 24 for studies of base-catalyzed reactions of such compounds. These workers reported that the DMSO procedure gave better yields than the old procedure using N 2 O 3 , which has not been employed recently.…”
Section: From Bromodicarbonylsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversion of β-dicarbonyl compounds to monobromo derivatives followed by replacement of bromine has received a new lease on life with the introduction of dimethyl sulfoxide as a mild reagent for replacing such activated bromine atoms by a carbonyl oxygen. These include 1,1-dimethyl-1,4-diphenylbutanetrione (15), used by Wolfe et al 25 in their investigation of possible helical conformations of the trione chain (see section VII.B), and a variety of simple triones (R 1 ) alkyl, aryl; R 2 ) alkyl, aryl, ester), prepared by Dahn and co-workers 24 for studies of base-catalyzed reactions of such compounds. These workers reported that the DMSO procedure gave better yields than the old procedure using N 2 O 3 , which has not been employed recently.…”
Section: From Bromodicarbonylsmentioning
confidence: 99%
“…Both bond lengths and bond angles could be modified as compared with simple carbonyl compounds. In addition, the justifiable assumption 25 (see below) that rotational barriers about the intercarbonyl single bonds will be small means that chains of carbonyl groups can adopt a variety of conformations. Of particular interest is the possibility of helical (ergo chiral) conformations.…”
Section: Structures Of Polyketones Theory and Experiments (Figure 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…The conformational surface was calculated using the CNINDO program (14). An actual analytic approximation of this E(o,,o,) surface by trigonometric functions is published elsewhere (13). The o, = o, = 0 conformation is defined by 1.…”
Section: Resultsmentioning
confidence: 99%
“…The final yield after extraction and distillation of the reaction mass was 67% (colourless oil, 146 °C/0.75 torr 18 . 2-Methyl-2-phenylpropanal used as a precursor in the synthesis of 3-DMDCN was obtained by a Grignard reaction between methyl mandelate and CH 3 I with pinacol formation (78%), followed by H 2 SO 4 /AcOH/I 2 treatment (yield ~60%), as described by Wolfe et al 19 The aldehyde was converted to 3-DMDCN with 61% yield by a . This compound was used as actinometer and for chromatographic and spectroscopic comparisons, as its photolysis rendered a single product.…”
Section: -Mdcnmentioning
confidence: 99%